A Zinc(II) Benzamidinate N‐Oxide Complex as an Aggregation‐Induced Emission Material: toward Solution‐Processable White Organic Light‐Emitting Devices. Issue 39 (11th October 2018) - Cibian, Mihela; Shahalizad, Afshin; Souissi, Fathi; Castro, Jessica; Ferreira, Janaina G.; Chartrand, Daniel; Nunzi, Jean‐Michel; Hanan, Garry S.
Abstract : The synthesis, characterization, photophysical and redox properties of a dinuclear complex Zn2 (AMOX)4 (AMOX = 4‐bromo‐ N, N′ ‐diphenylbenzamidinate N ‐oxide) are highlighted. This compound is a first example of a novel class of aggregation‐induced emission (AIE) materials. Noticeably, solution‐processed white‐green organic light‐emitting diodes were fabricated using this complex as dopant in a co‐host matrix in the emissive layer. A luminance efficiency and power efficiency as high as 1.12 cd/A and 0.30 lm/W were obtained, respectively. The characteristics of this complex: high solubility, thermal stability, AIE behaviour, ease of synthesis, tunability options, and low‐cost, reveal altogether great potential for the development of this new family of compounds as materials for applications in optoelectronic devices. Abstract : Zn2 (AMOX)4 is a prototype for new AIE materials based on the amidine N ‐oxide ligand platform. Solution‐processed white‐green OLEDs were fabricated using it as the dopant in the emissive layer. The high solubility and thermal stability, together with AIE behaviour, ease of synthesis, tunability options, and low‐cost demonstrate great potential for developing this family of compounds for optoelectronic applications.